Yrittäjyyden muodot ja tehtävä ajan murroksissa - Kyrö, Paula (1997)
This study describes the meaning and purpose of entrepreneurship as an everchanging reflection of culture, as a phenomenon searching for new forms in the course of history. The research problem was: How has the idea of entrepreneurship developed and why has this development taken place? The data consisted, on the one hand, of historical events and on the other, of the comprehension of entrepreneurship inherent in scientific models of economics, sociology and education. The postmodern methodology used in this study has allowed a reinterpretation of the understanding of entrepreneurship. In the course of history the nature of entrepreneurship has remained the same. It has always described innovative, holistic, risk-taking and co-ordinating ways of behaviour. In each era it has only focused its attention on the new, emerging phenomena. In the transition from traditional to modern this target has been on one hand the economic process at the macrolevel, on the other hand, the extraordinary individual producing this process. In the modern era the macrolevel has been lost and attention has been directed toward the small enterprise, where management and ownership are manifested in the same entity. ln the transition from modern to postmodern, entrepreneurship has again found a new object, now a product of the modern era, the organisation. Thus time itself has produced three different kinds of present-day entrepreneurship: 1. The small enterprise, meaning the individual entrepreneur and his firm, 2. Intrapreneurship, meaning an organisation's collective behaviour, 3. Individual, self-oriented entrepreneurship, meaning an individual's self-oriented behaviour. The shift in the paradigms of the theories can be identified in these forms. The first shift occurred when the economic process was lost and attention was addressed towards the small enterprise, the second when the organisation was selected as the target. Is the third shift about to occur, i.e. can entrepreneurship again find and connect with the economic process? This only the future can tell. Entrepreneurship has been found to be important and meaningful in society at two points of transition, first at the transition from traditional to modern, and now at the transition from modern to postmodern. The study has revealed, at both points of transitions, the latent, cultural role of entrepreneurship. It is suggested that the role of entrepreneurship can be regarded as an instrument for changing the culture of an era.